Metode K-Means Clustering Dalam Pengelompokan Penjualan Produk Frozen Food - Tifani Amalina; Danendra Bima Adhi Pramana; Betha Nurina Sari (Jurnal Ilmiah Wahana Pendidikan, 2022)
The creation of many businesses in the field of online-based sales or known as e-commerce is proof that internet technology is currently developing so rapidly in various industries, including business. Online shop is a business activity that uses E-Commerce in its marketing or trading operations. Knowing how interested consumers are in buying a product can be done by counting the number of sales transactions made, which is one of the information that can be collected. So that the increasing number of transaction activities by consumers there is very large and out of data. The results of this study indicate that the most optimal number of clusters is two clusters. From 45 frozen food product data, 3 frozen food products were found in cluster 1 and 42 frozen food products entered cluster 2. This study aims to apply the k-means clustering method in grouping frozen food sales to find out the grouping of consumer interest in a product. frozen food. It is hoped that this research can be useful for the company and as a reference for further research.